Factors Influencing the Success of Sustainable Food Home Area (KRPL) in Tanjunganom Sub-District, East Java Province, Indonesia - Prameswari, Tanjung; Sugiyanto, Sugiyanto; Yuliati, Yayuk; Kustanti, Asihing; Pintakami, Lintar Brillian (Universitas Panji Sakti, 2025)
Sustainable Food Home Area (KRPL) is a household-based food security initiative program. The use of yard land through KRPL activities has been carried out since 2010, encouraging the community to meet its food consumption needs independently and support household-scale food security. In some locations, KRPL activities have not reached their full potential, limiting the achievement of the program's objectives. This study was conducted to analyze the influence of internal and external factors on the success of KRPL activities among KRPL participants. Respondents were selected using a saturated sample, namely 22 women farmers who participated in KRPL activities in Getas Village, Tanjunganom District. Data analysis was conducted using ordinal logistic regression with the aid of SPSS 30 software. The study's results indicated that age in the range of ≤40 years, a time expenditure of 1.5-3 hours/day, and POMOSDA support fall into the medium category, which affects the success of KRPL activities in Getas Village. Spending 1.5–3 hours/day is the factor with the strongest influence, with an opportunity ratio value of (-12,316) = 4,485. This research is beneficial for women farmers who participate in KRPL activities because women farmers can determine the success of KRPL activities, and further guidance needs to be provided to determine the sustainability and implementation of yard land management systems obtained from extension workers (the government) and POMOSDA (the private sector) to face food security challenges, especially at the household scale.